INNOVATION CAPABILITY OF CLUSTERS: Understanding the innovation of geographic business netowrks. - Bittencourt, Bruno Anicet; Zen, Aurora Carneiro; Prévot, Frèderic (Review of Business Management, 2019)
Purpose – This paper aims to explore innovation in geographic business networks and to propose a model of innovation capability of cluster. The premise is that innovation is a necessity for firms and relations inter firms is an alternative for it to occur. Among these relationships, clusters stand out, with studies showing that firms in clusters tend to be more innovative. Design/methodology/approach–This, we conducted an exploratory research with two clusters: emerging cluster of Alto do Camaquã, in Brazil and growing cluster of Sisteron, in France.The cases were analyzed from elements previously established in the literature: context, collective strategy, public policy, commercialization, pro-activity, external relations, transmission collaboration, assimilation, transformation and application of knowledge, governance, infrastructure, financial resources and human resources. Findings– We arrived to a model of cluster innovation capability, composed by the strategic management, relationships and learning, technological and marketing development and operational management. Originality/value–The proposed model is a dinamic model as capabilities vary in their intensities according to the development stage of the cluster and its maturity time.